حجیت ِقراءات پرتمنا عمادی کے اعتراضات:محمد طاہر رحیمی کی "دفاع ِقراءات"کا مطالعہ (Al-Qamar, 2018)
Variant Readings (Ikhtilāf-e-Qirāʻāt) is an important subject in the field of Qurānic sciences. Muslim tradition, in general, authenticates the variations of Qirāʻāt, but some modern scholars have negated the authenticity of these variations. A Pakistani scholar Tamannā Imādī in his book titled “Aʻjāz al-Quran-o-Ikhtilāf-e-Qirāʻāt” has endorsed this refutation of variations. His work is responded by Muhammad Tāhir Rahīmī in his “Difāʻ-e-Qirāʻāt”. This article reads Rahīmī’s work. It explores that Rahīmī has nicely countered Imādī’s arguments. It, ratifying the traditional stance on the subject, supports Rahīmī argumentation on the authenticity of variant readings.
Keywords: Variant Readings; Tamannā Imādī; Tāhir Rahīmī